A new method to electrical parameters identification of carbon fiber reinforced composites using lightning disturbances corresponding to subsequent return strokes. (August 2022) - Filik, Kamil; Oliwa, Rafał; Karnas, Grzegorz; Masłowski, Grzegorz; Bulanda, Katarzyna; Oleksy, Mariusz; Królczyk, Jolanta
Highlights: A new system and method for identifying electrical parameters of CFRP composites. Raw surge impedance estimation based on resistivity measured at low voltage. CFRP lightning resistance estimation based on non-destructive tests. Influence of composite resin additives on electrical parameters of samples is shown. Measurements made with both low DC and high lightning-type impulses currents. Abstract: Carbon fiber reinforced polymers (CFRPs) are modern materials increasingly used in the aerospace industry due to its excellent mechanical properties but there is still a lot to do to improve their electrical capabilities. The paper presents a new prototype measurement system and method for identifying electrical parameters of conductive composites using both: low DC electrical signals and high-current impulses of lightning nature. Detail presentation of the measurement setup and used techniques was made on prepared three types of CFRP laminate samples consisting of five carbon fabric layers each with different contents of flame retardant and carbon black conductive additives. The 4-electrode and Van der Pauw methods were used for low voltage measurements of volume and surface resistivity. 15 kA high-current pulses have been applied to determine composite sample parameters such as equivalent volume and surface resistivity, surge impedance, current distribution and damage immunity to the effects of the lightning-type currents.